Partisipasi Petani Karet Dalam Perlindungan Ekosistem Di Nagari Sumpur Kudus Kabupaten Sijunjung - Wiwid Elvanda; Hasdi Aimon (Universitas Negeri Padang, 2022)
This study aims to examine the effect of rubber farmers' environmental awareness, rubber farmer income, rubber farmer education, and rubber plantation area on rubber farmers' participation in ecosystem protection efforts in Nagari Sumpur Kudus.This type of research is quantitative research using secondary data in 2020. This study uses multiple linear analysis methods.The results of this study indicate that: (1) environmental awareness of rubber farmers has a significant effect on rubber farmers' participation in ecosystem protection efforts;(2) rubber farmers' income has a significant effect on rubber farmers' participation in ecosystem protection efforts;(3) rubber farmer education has a significant effect on rubber farmers' participation in ecosystem protection efforts;(4) the area of rubber plantations has a significant effect on the participation of rubber farmers in efforts to protect the ecosystem.